Subsurface Analysis on Ranu Grati Lineaments with Satellite Gravity Data - Dhea Pratama Novian Putra; M. Haris Miftakhul Fajar; Dwa Desa Warnana; Amien Widodo; Faqih Ulumuddin; Syabibah Zakiyya Zukhrufah (Postgraduate, University of Mataram, 2023)
The lineaments with NE-SW direction formed by the Umbulan Spring, Banyubiru Spring, and Ranu Grati Maar in Pasuruan Regency indicate a geological structure. This structure is predicted to play a role in forming these springs and maar. Therefore, a study was conducted to identify the presence of these geological structures using the GGMPlus satellite gravity data. The data used in this study were 945 points with spacing intervals of about 200 to 300 meters. Satellite gravity data needs to be corrected so that the Complete Bouguer Anomaly (CBA) value is obtained, which can be used to determine the distribution of density contrast values ​​in the research area. Gridding is done by using a Second Vertical Derivative (SVD) filter to determine existing fault that results in the lineaments of the two springs and maar based on the second derivative value from CBA. It was found that the range of interpolated CBA values ​​in the study area was around 143 mGal to 150 mGal. SVD analysis indicates existing a fault plane exists through Umbulan Springs, Banyubiru Springs, and Ranu Grati Maar with E-W direction.